The CaALAD Gene From Pepper (Capsicum annuum L.) Confers Chilling Stress Tolerance in Transgenic Arabidopsis Plants - Wang, Huiping; Liu, Zeci; Xie, Jianming; Li, Jing; Zhang, Jing; Yu, Jihua; Hu, Linli; Zhang, Guobin (Frontiers in Plant Science, 2022)
The ALAD gene encodes an enzyme that is essential for chlorophyll biosynthesis and is involved in many other physiological processes in plants. In this study, the CaALAD gene was cloned from pepper and sequenced. Multiple sequence alignment and phylogenetic analysis of ALAD proteins from nine plant species showed that ALAD is highly conserved, and that CaALAD shows the highest homology with the ALAD protein from eggplant. Subcellular localization indicated that the CaALAD protein is mainly localized to the chloroplasts. After transferring CaALAD into the Arabidopsis thaliana genome, cold tolerance of the transgenic lines improved. Overexpression of CaALAD increased the relative transcription of the AtCBF2, AtICE1, and AtCOR15b genes in transgenic Arabidopsis plants exposed to low temperature (4oC) stress, and the contents of reactive oxygen species decreased due to increased activities of superoxide dismutase (SOD), peroxidase (POD), and catalase (CAT). Moreover, chlorophyll biosynthesis, as determined by the contents of porphobilinogen, protoporphyrin IX, Mg-protoporphyrin IX, prochlorophyllate, and chlorophyll in the transgenic Arabidopsis plants, increased in response to low temperature stress. In addition, the transgenic lines were more sensitive to exogenous ALA and NaHS, and the H2S content of transgenic line plants increased more rapidly than in the wild-type (WT), suggesting that CaALAD may respond to low temperatures by influencing the content of H2S, a signaling molecule. Our study gives a preliminary indication of the function of CaALAD and will provide a theoretical basis for future molecular breeding of cold tolerance in pepper.